Non-aqueous electrolyte secondary battery
By using a specific combination of graphite particles with controlled porosity and a carboxylic acid ester in the nonaqueous electrolyte, the nonaqueous electrolyte secondary battery effectively addresses the issue of capacity loss during fast charging cycles, maintaining battery performance and cycle characteristics.
Patent Information
- Application Number
- JP2021563834
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-09
- Filing Date
- 2020-11-25
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2040-11-25
AI Technical Summary
Conventional nonaqueous electrolyte secondary batteries experience a decrease in battery capacity when subjected to fast charging cycles due to the deterioration of rapid charging cycle characteristics.
The battery incorporates graphite particles A with an internal porosity of 5% or less and graphite particles B with an internal porosity of 8% to 20%, with graphite particles A predominantly on the outer surface half of the negative electrode current collector side, and a nonaqueous electrolyte containing a carboxylic acid ester represented by a specific general formula.
This configuration effectively suppresses the deterioration of fast charging cycle characteristics by reducing electrolyte decomposition and ensuring better adhesion and permeability, thereby maintaining battery performance under harsh charging conditions.
Smart Images

Figure 0007665528000006 
Figure 0007665528000007 
Figure 0007665528000008
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a non-aqueous electrolyte secondary battery. [Background technology]
[0002] 2. Description of the Related Art Non-aqueous electrolyte secondary batteries that use a carbon material as a negative electrode active material are widely used as high energy density secondary batteries.
[0003] For example, Patent Document 1 discloses a non-aqueous electrolyte secondary battery that uses densified carbon having an internal porosity of 5% or less as a carbon material.
[0004] For example, Patent Document 2 discloses a nonaqueous electrolyte secondary battery that uses carbon materials including carbon material A having an internal porosity of 1% or more and less than 23% and carbon material B having an internal porosity of 23% or more and 40% or less. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 9-320600 [Patent Document 2] JP 2014-67638 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, conventional non-aqueous electrolyte secondary batteries have a problem in that when a rapid charging cycle is performed in which charging is performed at a high rate to shorten the charging time, the battery capacity decreases.
[0007] Therefore, an object of the present disclosure is to provide a nonaqueous electrolyte secondary battery capable of suppressing deterioration of rapid charging cycle characteristics. [Means for solving the problem]
[0008] A nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure comprises a positive electrode, a negative electrode, and a nonaqueous electrolyte, the negative electrode comprising a negative electrode current collector and a negative electrode active material layer provided on the negative electrode current collector, the negative electrode active material layer comprising graphite particles A and graphite particles B as negative electrode active materials, the graphite particles A having an internal porosity of 5% or less and the graphite particles B having an internal porosity of 8% to 20%, the graphite particles A being contained in a larger amount in an outer surface half region than in an anode current collector half region when the negative electrode active material layer is divided into two equal parts in a thickness direction, the nonaqueous electrolyte comprising a nonaqueous solvent containing a carboxylate ester represented by the following general formula (I), and the carboxylate ester being contained in an amount of 5% to 50% by volume with respect to the entire nonaqueous solvent: [ka] (In the formula, R1 and R2 are each independently a hydrocarbon group having 2 or less carbon atoms.) Effect of the Invention
[0009] According to one embodiment of the present disclosure, it is possible to suppress deterioration of rapid charging cycle characteristics. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of a negative electrode according to an embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view of a graphite particle in a negative electrode active material layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] A nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure comprises a positive electrode, a negative electrode, and a nonaqueous electrolyte, the negative electrode comprising a negative electrode current collector and a negative electrode active material layer provided on the negative electrode current collector, the negative electrode active material layer comprising graphite particles A and graphite particles B as negative electrode active materials, the graphite particles A having an internal porosity of 5% or less and the graphite particles B having an internal porosity of 8% to 20%, the graphite particles A being contained in a larger amount in an outer surface half region than in an anode current collector half region when the negative electrode active material layer is divided into two equal parts in a thickness direction, the nonaqueous electrolyte comprising a nonaqueous solvent containing a carboxylate ester represented by the following general formula (I), and the carboxylate ester being contained in an amount of 5% to 50% by volume with respect to the entire nonaqueous solvent: [ka] (In the formula, R1 and R2 are each independently a hydrocarbon group having 2 or less carbon atoms.)
[0012] The graphite particles A with an internal porosity of 5% or less suppress the decomposition reaction of the non-aqueous electrolyte compared to the graphite particles with an internal porosity of more than 5%. Since the decomposition reaction of the non-aqueous electrolyte mainly occurs on the surface of the negative electrode, it is considered that the decomposition reaction of the non-aqueous electrolyte is suppressed even under harsh conditions such as rapid charging by including more graphite particles A with an internal porosity of 5% or less in the outer surface half of the negative electrode active material layer than in the negative electrode current collector half of the negative electrode active material layer as in the present disclosure. On the other hand, the graphite particles A with an internal porosity of 5% or less are difficult to crush when forming an electrode, and therefore have a lower binding property with the negative electrode current collector compared to the graphite particles with an internal porosity of more than 5%. However, in the present disclosure, since there are few graphite particles A with an internal porosity of 5% or less in the negative electrode current collector side half region of the negative electrode active material layer, it is believed that the adhesion between the negative electrode current collector and the graphite particles is easily ensured, and the graphite particles are unlikely to peel off from the negative electrode current collector even under harsh conditions such as rapid charging. Furthermore, it is believed that a nonaqueous electrolyte solution containing a predetermined amount of the above-mentioned carboxylate ester has a lower viscosity and improved permeability into the positive and negative electrode active material layers compared to a nonaqueous electrolyte solution not containing the above-mentioned carboxylate ester, and therefore an efficient battery reaction occurs even under harsh conditions such as rapid charging. For these reasons, it is believed that the nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure suppresses the deterioration of rapid charging cycle characteristics.
[0013] Hereinafter, an example of an embodiment will be described in detail with reference to the drawings. Note that the nonaqueous electrolyte secondary battery of the present disclosure is not limited to the embodiment described below. Also, the drawings referred to in the description of the embodiment are schematic.
[0014] FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery according to an embodiment. The nonaqueous electrolyte secondary battery 10 shown in FIG. 1 includes a wound electrode body 14 formed by winding a positive electrode 11 and a negative electrode 12 with a separator 13 therebetween, a nonaqueous electrolyte, insulating plates 18 and 19 respectively arranged above and below the electrode body 14, and a battery case 15 for accommodating the above-mentioned components. The battery case 15 is composed of a bottomed cylindrical case body 16 and a sealing body 17 for closing the opening of the case body 16. Note that, instead of the wound electrode body 14, an electrode body of another form may be applied, such as a laminated electrode body formed by alternately stacking positive and negative electrodes with a separator interposed therebetween. In addition, examples of the battery case 15 include a metallic outer can such as a cylindrical, square, coin, or button-shaped one, and a pouch outer body formed by laminating a resin sheet and a metal sheet.
[0015] The case body 16 is, for example, a metallic outer can having a cylindrical shape with a bottom. A gasket 28 is provided between the case body 16 and the sealing body 17 to ensure airtightness inside the battery. The case body 16 has a protruding portion 22 that supports the sealing body 17, for example, a part of the side surface of the case body 16 protruding inward. The protruding portion 22 is preferably formed in an annular shape along the circumferential direction of the case body 16, and supports the sealing body 17 on its upper surface.
[0016] The sealing body 17 has a structure in which a filter 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cap 27 are laminated in this order from the electrode body 14 side. Each member constituting the sealing body 17 has, for example, a disk shape or a ring shape, and each member except the insulating member 25 is electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected to each other at their respective centers, and the insulating member 25 is interposed between their respective peripheral edges. When the internal pressure of the nonaqueous electrolyte secondary battery 10 increases due to heat generation caused by an internal short circuit or the like, for example, the lower valve body 24 deforms and breaks so as to push the upper valve body 26 toward the cap 27, and the current path between the lower valve body 24 and the upper valve body 26 is interrupted. When the internal pressure further increases, the upper valve body 26 breaks, and gas is discharged from the opening of the cap 27.
[0017] 1, a positive electrode lead 20 attached to a positive electrode 11 passes through a through hole in an insulating plate 18 and extends toward a sealing body 17, and a negative electrode lead 21 attached to a negative electrode 12 passes outside an insulating plate 19 and extends toward the bottom side of a case body 16. The positive electrode lead 20 is connected to the underside of a filter 23, which is the bottom plate of the sealing body 17, by welding or the like, and a cap 27, which is the top plate of the sealing body 17 and is electrically connected to the filter 23, serves as a positive electrode terminal. The negative electrode lead 21 is connected to the inner bottom surface of the case body 16 by welding or the like, and the case body 16 serves as a negative electrode terminal.
[0018] Each of the components of the nonaqueous electrolyte secondary battery 10 will now be described in detail.
[0019] [Negative electrode] 2 is a cross-sectional view of a negative electrode according to an embodiment of the present invention. The negative electrode 12 includes a negative electrode current collector 40 and a negative electrode active material layer 42 provided on the negative electrode current collector 40.
[0020] The negative electrode current collector 40 may be, for example, a foil of a metal such as copper that is stable in the potential range of the negative electrode, or a film having such a metal disposed on its surface.
[0021] The negative electrode active material layer 42 contains graphite particles as the negative electrode active material. The negative electrode active material layer 42 preferably contains a binder and the like. The negative electrode 12 can be produced, for example, by preparing a negative electrode mixture slurry containing the negative electrode active material, the binder and the like, applying the negative electrode mixture slurry onto the negative electrode current collector 40, drying the slurry to form the negative electrode active material layer 42, and rolling the negative electrode active material layer 42. The method for producing the negative electrode active material layer 42 will be described in detail later.
[0022] Fig. 3 is a cross-sectional view of a graphite particle in a negative electrode active material layer. As shown in Fig. 3, a graphite particle 30 has, in a cross-sectional view of the graphite particle 30, closed voids 34 that do not connect the inside of the particle to the particle surface (hereinafter, internal voids 34) and voids 36 that connect the inside of the particle to the particle surface (hereinafter, external voids 36).
[0023] The graphite particles 30 in this embodiment include graphite particles A having an internal porosity of 5% or less and graphite particles B having an internal porosity of 8% to 20%. The internal porosity of the graphite particles A may be 5% or less in order to suppress the deterioration of the rapid charging cycle characteristics, but is preferably 1% to 5%, and more preferably 3% to 5%. The internal porosity of the graphite particles B may be 8% to 20% in order to suppress the deterioration of the rapid charging cycle characteristics, but is preferably 10% to 18%, and more preferably 12% to 16%. Here, the internal porosity of the graphite particles is a two-dimensional value calculated from the ratio of the area of the internal voids 34 of the graphite particles to the cross-sectional area of the graphite particles. The internal porosity of the graphite particles is calculated by the following procedure.
[0024] <Method for measuring internal porosity> (1) Exposing a cross section of the negative electrode active material layer. For example, a method for exposing the cross section includes cutting out a part of the negative electrode and processing it with an ion milling device (e.g., IM4000PLUS manufactured by Hitachi High-Technologies Corporation) to expose the cross section of the negative electrode active material layer. (2) A backscattered electron image of the cross section of the exposed negative electrode active material layer is taken using a scanning electron microscope at a magnification of 3,000 to 5,000 times. (3) The cross-sectional image obtained as described above is imported into a computer and binarized using image analysis software (e.g., ImageJ, manufactured by the National Institutes of Health, USA) to obtain a binary processed image in which the particle cross-sections in the cross-sectional image are colored black and voids present in the particle cross-sections are colored white. (4) From the binarized image, graphite particles A and B with a particle size of 5 μm to 50 μm are selected, and the area of the graphite particle cross section and the area of the internal voids present in the graphite particle cross section are calculated. Here, the area of the graphite particle cross section refers to the area of the region surrounded by the outer periphery of the graphite particle, that is, the area of the entire cross section of the graphite particle. In addition, for voids present in the graphite particle cross section that have a width of 3 μm or less, it may be difficult to distinguish whether they are internal voids or external voids in image analysis, so voids with a width of 3 μm or less may be considered internal voids. Then, the internal void ratio of the graphite particle (area of internal voids in graphite particle cross section × 100 / area of graphite particle cross section) is calculated from the calculated area of the graphite particle cross section and the area of the internal voids in the graphite particle cross section. The internal void ratios of graphite particles A and B are the average values of 10 graphite particles A and B, respectively.
[0025] The graphite particles A and B are produced, for example, as follows. <Graphite particles A with internal porosity of 5% or less> For example, the coke (precursor) as the main raw material is crushed to a predetermined size, and then the crushed coke is agglomerated with a binder, baked at a temperature of 2600°C or higher, graphitized, and sieved to obtain graphite particles A of a desired size. Here, the internal porosity can be adjusted to 5% or less depending on the particle size of the crushed precursor or the particle size of the agglomerated precursor. For example, the average particle size (volume-based median diameter D50) of the crushed precursor is preferably in the range of 12 μm to 20 μm. In addition, when the internal porosity is reduced to a range of 5% or less, it is preferable to increase the particle size of the crushed precursor. <Graphite particles B with internal porosity of 8% to 20%> For example, the coke (precursor) as the main raw material is crushed to a predetermined size, agglomerated with a binder, and then pressed into a block shape, which is then fired at a temperature of 2600°C or higher to be graphitized. The graphitized block-shaped body is crushed and sieved to obtain graphite particles B of a desired size. Here, the internal porosity can be adjusted to 8% to 20% depending on the amount of volatile components added to the block-shaped body. When a part of the binder added to the coke (precursor) volatilizes during firing, the binder can be used as the volatile component. An example of such a binder is pitch.
[0026] The graphite particles A and B used in this embodiment may be natural graphite, artificial graphite, or the like, but are not particularly limited thereto. However, in terms of ease of adjusting the internal porosity, artificial graphite is preferred. The interplanar spacing (d 002 ) is, for example, preferably 0.3354 nm or more, more preferably 0.3357 nm or more, and preferably less than 0.340 nm, more preferably 0.338 nm or less. The crystallite size (Lc(002)) of the graphite particles A and B used in this embodiment, determined by X-ray diffraction, is, for example, preferably 5 nm or more, more preferably 10 nm or more, and preferably 300 nm or less, more preferably 200 nm or less. The interplanar spacing (d 002 When the crystallite size (Lc(002)) satisfies the above range, the battery capacity of the nonaqueous electrolyte secondary battery tends to be larger than when the crystallite size (Lc(002)) does not satisfy the above range.
[0027] In this embodiment, when the negative electrode active material layer 42 shown in Fig. 2 is divided into two equal parts in the thickness direction, the graphite particles A are contained more in the outer surface half region 42b than in the negative electrode current collector half region 42a. This suppresses, for example, decomposition of the nonaqueous electrolyte and peeling of the graphite particles from the negative electrode current collector 40 during a rapid charging cycle, thereby suppressing a decrease in rapid charging cycle characteristics. Note that dividing the negative electrode active material layer 42 into two equal parts in the thickness direction means that when the stacking direction of the negative electrode current collector 40 and the negative electrode active material layer 42 is the thickness direction of the negative electrode active material layer 42, the negative electrode active material layer 42 is divided into two equal parts at the middle Z of the thickness of the negative electrode active material layer 42. The negative electrode active material layer 42 is divided into two equal parts in the thickness direction, and the negative electrode active material layer 42 located closer to the negative electrode current collector 40 is defined as the negative electrode current collector side half region 42a, and the negative electrode active material layer 42 located farther from the negative electrode current collector 40 is defined as the outer surface side half region 42b.
[0028] In this embodiment, it is sufficient that the graphite particles A are contained more in the outer surface half region 42b than in the negative electrode current collector half region 42a, but in order to further suppress the deterioration of the rapid charge cycle characteristics, the ratio of the graphite particles A to the graphite particles B in the outer surface half region 42b is preferably 20:80 to 100:0 by mass, and more preferably 50:50 to 100:0. Also, in order to further suppress the deterioration of the rapid charge / discharge cycle characteristics, the ratio of the graphite particles A to the graphite particles B in the negative electrode current collector half region 42a is preferably 10:90 to 0:100 by mass, and more preferably 0:100.
[0029] An example of a method for producing the negative electrode active material layer 42 will be described. For example, a negative electrode active material containing graphite particles B (graphite particles A as required), a binder, and a solvent such as water are mixed to prepare a negative electrode composite material slurry for the negative electrode current collector side. Separately, a negative electrode active material containing a larger amount of graphite particles A (graphite particles B as required) than the negative electrode composite material slurry for the negative electrode current collector side is mixed with a binder and a solvent such as water to prepare a negative electrode composite material slurry for the outer surface side. Then, the negative electrode composite material slurry for the negative electrode current collector side is applied to both sides of the negative electrode current collector and dried, and then the negative electrode composite material slurry for the outer surface side is applied to both sides of the coating film made of the negative electrode composite material slurry for the negative electrode current collector side and dried, thereby forming the negative electrode active material layer 42. In the above-described method, the negative electrode composite slurry for the negative electrode current collector side is applied and dried, and then the negative electrode composite slurry for the outer surface side is applied. However, a method in which the negative electrode composite slurry for the outer surface side is applied after the negative electrode composite slurry for the negative electrode current collector side is applied and before drying may be used, or the negative electrode composite slurry for the negative electrode current collector side and the negative electrode composite slurry for the outer surface side may be applied simultaneously.
[0030] The negative electrode active material may contain, in addition to the graphite particles A and B used in this embodiment, other materials capable of reversibly absorbing and releasing lithium ions, for example, a Si-based material. Examples of the Si-based material include Si, an alloy containing Si, and SiO x (x is 0.8 to 1.6) and the like. The Si-based material is a negative electrode material capable of improving the battery capacity more than graphite particles, but on the other hand, it is disadvantageous in terms of rapid charging cycle characteristics because of its large volume expansion accompanying charging and discharging. However, in a negative electrode active material layer having a negative electrode active material containing graphite particles A and B and a Si-based material, the amount of graphite particles A is made larger in the outer surface half region than in the negative electrode current collector half region, which can suppress the deterioration of rapid charging cycle characteristics compared to the case where the graphite particles A are uniformly dispersed in the negative electrode active material layer. The content of the Si-based material is, for example, preferably 1 mass% to 10 mass%, more preferably 3 mass% to 7 mass%, relative to the mass of the negative electrode active material, in terms of improving the battery capacity and suppressing the deterioration of rapid charging cycle characteristics.
[0031] Other examples of the other material capable of reversibly absorbing and releasing lithium ions include metals that are alloyed with lithium, such as tin (Sn), and alloys and oxides containing metal elements such as Sn. The negative electrode active material may contain the other materials, and the content of the other materials is desirably, for example, 10% by mass or less with respect to the mass of the negative electrode active material.
[0032] Examples of the binder include fluorine-based resin, PAN, polyimide-based resin, acrylic resin, polyolefin-based resin, styrene-butadiene rubber (SBR), nitrile-butadiene rubber (NBR), carboxymethyl cellulose (CMC) or a salt thereof, polyacrylic acid (PAA) or a salt thereof (PAA-Na, PAA-K, etc., or a partially neutralized salt), polyvinyl alcohol (PVA), etc. These may be used alone or in combination of two or more kinds.
[0033] [Positive electrode] The positive electrode 11 is composed of a positive electrode current collector such as a metal foil and a positive electrode active material layer formed on the positive electrode current collector. The positive electrode current collector may be a foil of a metal such as aluminum that is stable in the potential range of the positive electrode, or a film having the metal disposed on the surface layer. The positive electrode active material layer includes, for example, a positive electrode active material, a binder, a conductive material, and the like.
[0034] The positive electrode 11 can be produced, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive material, etc. onto a positive electrode current collector, drying it to form a positive electrode active material layer, and then rolling this positive electrode active material layer.
[0035] The positive electrode active material may be, for example, a lithium transition metal oxide containing a transition metal element such as Co, Mn, or Ni. x CoO2, Li x NiO2, Li x MnO2, Li x Co y Ni 1-y O2, Li x Co y M 1-y O z , Lix Ni 1-y M y O z 、 Li x Mn2O4, Li x Mn 2-y M y O4, LiMPO4, Li2MPO4F (M; at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0 < x ≤ 1.2, 0 < y ≤ 0.9, 2.0 ≤ z ≤ 2.3). These may be used alone or in combination of multiple types. In terms of achieving high capacity of the non-aqueous electrolyte secondary battery, the positive electrode active material is Li x NiO2, Li x Co y Ni 1-y O2, Li x Ni 1-y M y O z (M; at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0 < x ≤ 1.2, 0 < y ≤ 0.9, 2.0 ≤ z ≤ 2.3), etc. lithium nickel composite oxides are preferably included.
[0036] The conductive material includes, for example, carbon-based particles such as carbon black (CB), acetylene black (AB), ketjen black, graphite, etc. These may be used alone or in combination of two or more types.
[0037] The binder includes, for example, fluorine-based resins such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide-based resins, acrylic resins, polyolefin-based resins, etc. These may be used alone or in combination of two or more types.
[0038] [Non-aqueous electrolyte] The non-aqueous electrolyte has a non-aqueous solvent containing a carboxylic acid ester represented by the following general formula (I). And the carboxylic acid ester represented by the following general formula (I) is contained in an amount of 5% to 50% by volume based on the total non-aqueous solvent. [ka] (In the formula, R1 and R2 are each independently a hydrocarbon group having 2 or less carbon atoms.)
[0039] By using a non-aqueous electrolyte solution containing a predetermined amount of the carboxylic acid ester represented by the above general formula (I), for example, the viscosity of the non-aqueous electrolyte solution is reduced, improving the permeability into the positive and negative electrode active material layers, so that an efficient battery reaction occurs even under harsh conditions such as rapid charging, and the deterioration of rapid charging cycle characteristics is suppressed. If the content of the carboxylic acid ester represented by the above general formula (I) exceeds 50% by volume relative to the entire non-aqueous solvent, for example, the decomposition reaction of the non-aqueous electrolyte solution is likely to occur, and the deterioration of rapid charging cycle characteristics cannot be sufficiently suppressed. The content of the carboxylic acid ester represented by the above general formula (I) is preferably in the range of 30% by volume to 50% by volume, more preferably in the range of 35% by volume to 45% by volume, relative to the entire non-aqueous solvent, in terms of suppressing the deterioration of rapid charging cycle characteristics and showing excellent battery resistance in a low-temperature environment.
[0040] Examples of the hydrocarbon group having 2 or less carbon atoms include an alkyl group having 2 or less carbon atoms, an alkynyl group having 2 carbon atoms, and an alkenyl group having 2 carbon atoms. Examples of the alkyl group having 2 or less carbon atoms include a methyl group and an ethyl group. Examples of the alkynyl group having 2 carbon atoms include an ethynyl group. Examples of the alkenyl group having 2 carbon atoms include an ethenyl group. The hydrogen atoms of the alkyl group, the alkenyl group, and the alkynyl group may be substituted with a different element as necessary. Examples of the different element include, but are not limited to, fluorine, chlorine, bromine, and the like.
[0041] Examples of the carboxylate ester represented by the general formula (I) include methyl acetate, ethyl acetate, methyl propionate, and ethyl propionate. Among these, methyl acetate is preferred in terms of further suppressing the deterioration of the rapid charging cycle characteristics. These may be used alone or in combination of two or more.
[0042] The non-aqueous solvent may contain, for example, a non-aqueous solvent other than the carboxylic acid ester represented by the above general formula (I). For example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more of these can be used as the other non-aqueous solvent. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen atoms of these solvents are substituted with halogen atoms such as fluorine.
[0043] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, chain carbonates such as dimethyl carbonate (DMC), methyl ethyl carbonate (MEC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, cyclic carboxylates such as γ-butyrolactone, γ-valerolactone, chain carboxylates such as propyl acetate, propyl propionate, etc. The chain carboxylates are other than the carboxylates represented by the general formula (I) above.
[0044] Examples of the above-mentioned ethers include cyclic ethers such as 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, crown ether, etc., and chain ethers such as 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, etc.
[0045] As the above-mentioned halogenated derivatives, it is preferable to use fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, etc.
[0046] The non-aqueous electrolyte contains an electrolyte salt. The electrolyte salt is preferably a lithium salt. Examples of the lithium salt include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10 , LiCl, LiBr, LiI, lithium chloroborane, lithium lower aliphatic carboxylate, borate salts such as Li2B4O7, Li(B(C2O4)F2), LiN(SO2CF3)2, LiN(C1F2l+1 SO2)(C m F 2m+1 SO2){l, m are integers of 0 or more} and other imide salts. The lithium salt may be used alone or in combination. Among these, LiPF6 is preferably used from the viewpoints of ion conductivity, electrochemical stability, and the like. The concentration of the lithium salt is preferably 0.8 to 1.8 mol per 1 L of the non-aqueous solvent.
[0047] The viscosity of the non-aqueous electrolyte is, for example, preferably 3.1 cP or less, more preferably 2.8 cP or less, and even more preferably 2.5 cP or less, in order to further suppress the deterioration of the rapid charging cycle characteristics.
[0048] [Separator] For example, a porous sheet having ion permeability and insulation is used for the separator 13. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The separator is preferably made of an olefin resin such as polyethylene or polypropylene, or cellulose. The separator 13 may be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin. Alternatively, the separator may be a multilayer separator including a polyethylene layer and a polypropylene layer, and a separator having a surface coated with a material such as an aramid resin or ceramic may be used. EXAMPLES
[0049] The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.
[0050] <Example 1> [Preparation of positive electrode] The positive electrode active material is aluminum-containing lithium nickel cobalt oxide (LiNi 0.88 Co 0.09 Al 0.03O2) was used. 100 parts by mass of the above positive electrode active material, 1 part by mass of acetylene black, and 0.9 parts by mass of polyvinylidene fluoride were mixed in a solvent of N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode composite slurry. This slurry was applied to both sides of an aluminum foil having a thickness of 15 μm, and the coating film was dried and then rolled with a rolling roller to produce a positive electrode in which a positive electrode active material layer was formed on both sides of the positive electrode current collector. The produced positive electrode was cut to a width of 57.6 mm and a length of 679 mm for use.
[0051] [Preparation of graphite particles A] The coke was pulverized until the average particle size (median diameter D50) was 12 μm. Pitch was added as a binder to the pulverized coke, and the coke was aggregated until the average particle size (median diameter D50) was 17 μm. The aggregate was graphitized by baking at a temperature of 2800° C., and then sieved using a 250 mesh sieve to obtain graphite particles A with an average particle size (median diameter D50) of 23 μm.
[0052] [Preparation of graphite particles B] The coke was crushed to an average particle size (median diameter D50) of 15 μm, and the crushed coke was agglomerated by adding pitch as a binder. The coke was then subjected to an isostatic pressure of 1.6 g / cm. 3 ~1.9g / cm 3 A block-shaped compact having a density of 1000 nm was produced. This block-shaped compact was graphitized by firing at a temperature of 2800° C. Next, the graphitized block-shaped compact was pulverized and sieved using a 250 mesh sieve to obtain graphite particles B having an average particle size (median size D50) of 23 μm.
[0053] [Preparation of negative electrode] Graphite particles A were mixed to 40 parts by mass, graphite particles B were mixed to 55 parts by mass, and SiO was mixed to 5 parts by mass, which was used as the negative electrode active material A contained in the outer surface side half region of the negative electrode active material layer. These were mixed so that the mass ratio of negative electrode active material A: carboxymethylcellulose (CMC): styrene-butadiene copolymer rubber (SBR) was 100:1:1 to prepare a negative electrode mixture slurry on the outer surface side. In addition, graphite particles B were mixed to 95 parts by mass, and SiO was mixed to 5 parts by mass, which was used as the negative electrode active material B contained in the negative electrode current collector side half region of the negative electrode active material layer. These were mixed so that the mass ratio of negative electrode active material B: carboxymethylcellulose (CMC): styrene-butadiene copolymer rubber (SBR) was 100:1:1 to prepare a negative electrode mixture slurry on the negative electrode current collector side.
[0054] The negative electrode mixture slurry on the negative electrode current collector side was applied to both sides of a copper foil with a thickness of 8 μm, the coating was dried, and then the negative electrode mixture slurry on the outer surface side was applied on the coating, dried, and the coating was rolled with a rolling roller to produce a negative electrode in which a negative electrode active material layer was formed on both sides of the negative electrode current collector. That is, the graphite particles A: graphite particles B in the outer surface half of the negative electrode active material layer were in a mass ratio of 40:55, and the graphite particles A: graphite particles B in the negative electrode current collector half of the negative electrode active material layer were in a mass ratio of 0:100. In addition, the internal porosity of the graphite particles A and B in the produced negative electrode was measured and found to be 3% and 15%, respectively. The produced negative electrode was cut to a width of 58.6 mm and a length of 662 mm for use.
[0055] [Preparation of non-aqueous electrolyte] LiPF6 was dissolved at a concentration of 1.3 mol / L in a non-aqueous solvent in which ethylene carbonate (EC), methyl ethyl carbonate (MEC), dimethyl carbonate (DMC), and methyl acetate (MA) were mixed in a volume ratio of 16:4:70:10. This was used as a non-aqueous electrolyte. The viscosity of the non-aqueous electrolyte in Example 1 was 2.8 cP. The viscosity of the non-aqueous electrolyte was measured using a rotational viscometer. The same applies to the following examples and comparative examples.
[0056] [Preparation of non-aqueous electrolyte secondary battery] (1) A positive electrode lead was attached to the positive electrode current collector, and a negative electrode lead was attached to the negative electrode current collector. After that, the positive and negative electrodes were wound with a polyethylene separator interposed between them to prepare a wound type electrode body. (2) Insulating plates were placed above and below the electrode body, the negative electrode lead was welded to the case body, and the positive electrode lead was welded to the sealing member, and the electrode body was housed within the case body. (3) After the non-aqueous electrolyte was injected into the case body under reduced pressure, the open end of the case body was sealed with a sealing member via a gasket, completing the non-aqueous electrolyte secondary battery.
[0057] <Example 2> LiPF6 was dissolved at a concentration of 1.3 mol / L in a non-aqueous solvent in which ethylene carbonate (EC), methyl ethyl carbonate (MEC), dimethyl carbonate (DMC), and methyl acetate (MA) were mixed in a volume ratio of 14:3:53:30. This was used as a non-aqueous electrolyte. The viscosity of this non-aqueous electrolyte was 2.4 cP. In Example 2, a non-aqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that the non-aqueous electrolyte prepared above was used.
[0058] <Example 3> LiPF6 was dissolved at a concentration of 1.3 mol / L in a non-aqueous solvent in which ethylene carbonate (EC), methyl ethyl carbonate (MEC), dimethyl carbonate (DMC), and ethyl propionate (PE) were mixed in a volume ratio of 16:4:70:10. This was used as a non-aqueous electrolyte. The viscosity of this non-aqueous electrolyte was 3.1 cP. In Example 3, a non-aqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that the non-aqueous electrolyte prepared above was used.
[0059] <Comparative Example 1> LiPF6 was dissolved at a concentration of 1.3 mol / L in a non-aqueous solvent in which ethylene carbonate (EC), methyl ethyl carbonate (MEC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 20:5:75. This was used as a non-aqueous electrolyte. The viscosity of this non-aqueous electrolyte was 3.2 cP. In Comparative Example 1, a non-aqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that the non-aqueous electrolyte prepared above was used.
[0060] <Comparative Example 2> Graphite particles B were mixed to 95 parts by mass and SiO to 5 parts by mass, and this was used as the negative electrode active material C contained in the entire region of the negative electrode active material layer. The negative electrode active material C: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) were mixed so that the mass ratio was 100:1:1 to prepare a negative electrode mixture slurry. This negative electrode mixture slurry was applied to both sides of a copper foil with a thickness of 8 μm, the coating film was dried, and then the coating film was rolled with a rolling roller to prepare a negative electrode in which a negative electrode active material layer was formed on both sides of the negative electrode current collector. That is, the graphite particles A: graphite particles B in the outer surface side half region of the negative electrode active material layer was 0:100 in mass ratio, and the graphite particles A: graphite particles B in the negative electrode current collector side half region of the negative electrode active material layer was also 0:100 in mass ratio. The prepared negative electrode was cut to a width of 58.6 mm and a length of 662 mm for use.
[0061] In Comparative Example 2, a nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 1, except that the negative electrode fabricated above and the nonaqueous electrolyte prepared in Comparative Example 1 were used.
[0062] <Comparative Example 3> A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 1, except that the negative electrode fabricated in Comparative Example 1 was used.
[0063] [Measurement of capacity retention rate during rapid charging cycles] At an ambient temperature of 25°C, the nonaqueous electrolyte secondary batteries of each Example and Comparative Example were charged at a constant current of 1C (4600mA) to 4.2V, and then charged at a constant voltage of 1 / 50C at 4.2V. Thereafter, the batteries were discharged at a constant current of 0.5C to 2.5V. This charge / discharge cycle was counted as one cycle, and 100 cycles were performed. The capacity retention rate of the nonaqueous electrolyte secondary batteries of each Example and Comparative Example in the rapid charge cycle was calculated by the following formula. Capacity retention rate = (discharge capacity at 100th cycle / discharge capacity at 1st cycle) x 100
[0064] [Measurement of DC resistance in a low temperature environment] At an ambient temperature of 25°C, the nonaqueous electrolyte secondary batteries of each Example and Comparative Example were charged at a constant current of 0.3C (1C=4700mA) to 3.54V, and then charged at a constant voltage of 1 / 50C. After that, at an ambient temperature of -20°C, after resting for 2 hours, they were charged at a constant current of 0.3C to 3.54V. Then, they were discharged at 0.3C, and the voltage before discharge and the voltage 10 seconds after the start of discharge were measured. The measured voltage was applied to the following formula to calculate the direct current resistance (DCR) of each battery in a low-temperature environment. DCR(Ω)=(Voltage after 10 seconds - Voltage before discharge) / Current value
[0065] The results of the capacity retention rate in the rapid charge cycle and the DCR in a low temperature environment of the nonaqueous electrolyte secondary batteries of each Example and Comparative Example are summarized in Table 1. Note that the higher the value of the capacity retention rate in the rapid charge cycle, the more suppressed the deterioration of the rapid charge cycle characteristics.
[0066] [Table 1]
[0067] Comparing Comparative Examples 1 and 2, which have the same electrolyte composition, Comparative Example 1, which uses a negative electrode in which the graphite particles A are contained more in the outer surface half of the negative electrode current collector half when the negative electrode active material layer is divided into two equal parts in the thickness direction, has a higher capacity retention rate in the rapid charging cycle than Comparative Example 2, and the deterioration of the rapid charging cycle characteristics was suppressed. Furthermore, comparing Examples 1 to 3, which use the same negative electrode, and Comparative Example 1, Examples 1 to 3, which use a non-aqueous electrolyte containing 10 volume % or more of methyl acetate or ethyl propionate, have a higher capacity retention rate in the rapid charging cycle than Comparative Example 1, and the deterioration of the rapid charging cycle characteristics was suppressed. Among Examples 1 to 3, Examples 1 and 2, which use methyl acetate, have a higher capacity retention rate in the rapid charging cycle than Example 3, and the deterioration of the rapid charging cycle characteristics was suppressed. In particular, Example 2, which uses a non-aqueous electrolyte containing 30 volume % or more of methyl acetate, has the highest capacity retention rate in the rapid charging cycle. Furthermore, Example 2 had the lowest DCR value in a low temperature environment among the examples and comparative examples. [Explanation of symbols]
[0068] 10 nonaqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 15 battery case, 16 case body, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 protruding portion, 23 filter, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cap, 28 gasket, 30 graphite particles, 34 internal gap, 36 external gap, 40 negative electrode current collector, 42 negative electrode active material layer, 42a negative electrode current collector side half region, 42b outer surface side half region.
Claims
1. A non-aqueous electrolyte secondary battery having a positive electrode, a negative electrode, and a non-aqueous electrolyte, the negative electrode has a negative electrode current collector and a negative electrode active material layer provided on the negative electrode current collector, The negative electrode active material layer contains graphite particles A and graphite particles B as negative electrode active materials, the graphite particles A have an internal porosity of 5% or less, and the graphite particles B have an internal porosity of 8% to 20%, the graphite particles A are contained in a larger amount in an outer surface half region than in an outer surface half region of the negative electrode current collector side when the negative electrode active material layer is divided into two equal parts in a thickness direction; the negative electrode current collector side half region and the outer surface side half region contain 1 mass % to 10 mass % of a Si-based material with respect to the mass of the negative electrode active material, The nonaqueous electrolyte solution has a nonaqueous solvent containing a carboxylic acid ester represented by the following general formula (I): The nonaqueous electrolyte secondary battery comprises the carboxylate in an amount of 5 to 50% by volume based on the total volume of the nonaqueous solvent. 【Chemistry 1】 (In the formula, R1 and R2 are each independently a hydrocarbon group having 2 or less carbon atoms.)
2. 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein the carboxylate ester comprises methyl acetate.
3. 3. The nonaqueous electrolyte secondary battery according to claim 1, wherein the viscosity of the nonaqueous electrolyte is 3.1 cP or less.
Citation Information
Patent Citations
Secondary battery having nonaqueous solvent
JP1997171825A
Electrochemical battery fined carbon
JP1997320600A
Carbon material for nonaqueous secondary battery, negative electrode, and nonaqueous secondary battery
JP2014067638A
Negative electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery
WO2019187537A1